A Sistematic Literature Review : Implementasi Asesmen Diagnostik pada Kurikulum Merdeka - Nugroho, Dennis; Wirawan, Wirawan; Febriantania, Putri; Ridaningsih, Ida (STIT Muhammadiyah Paciran Lamongan, 2023)
This research aims to examine scientific articles that are relevant and related to the implementation of diagnostic assessments. The research method used in writing this article is a literature review. The literature review was obtained from articles published in the last 5 years, namely from 2019 to 2023. The literature search was focused on the keyword